Sistem Informasi Inventory Barang Berbasis Website dengan Metode Rapid Application Development (RAD) pada PT. Oasis Water International Bogor - Faizah, Siti; Pudji, Eni Pudji (Bahasa Indonesia, 2026)
PT. Oasis Water International is a company engaged in AMDK, which is Packaged Drinking Water. This research aims to design and build an information system that can manage inventory efficiently at PT. Oasis Water International, which operates in the field of packaged drinking water production. Currently, inventory management in the company is still carried out manually, using a non-integrated recording method, resulting in inefficiency, recording errors, and delays in data processing. The method used in this research is the First-In-First-Out (FIFO) method to ensure that the first goods to enter are the first to leave, thereby minimizing the risk of losses due to expired products. This research also uses the Rapid Application Development (RAD) approach in software development to accelerate the design and implementation process of the system. The results of this research are expected to can improve operational efficiency, reduce storage costs, and increase customer satisfaction by providing accurate and real-time information about inventory. With the implementation of this web-based information system, PT. Oasis Water International is expected to be able to address existing problems and improve performance as well as competitiveness in the bottled drinking water industry.